Π‐Conjugated Lewis Base: Efficient Trap‐Passivation and Charge‐Extraction for Hybrid Perovskite Solar Cells. Issue 7 (6th December 2016) - Lin, Yuze; Shen, Liang; Dai, Jun; Deng, Yehao; Wu, Yang; Bai, Yang; Zheng, Xiaopeng; Wang, Jiayu; Fang, Yanjun; Wei, Haotong; Ma, Wei; Zeng, Xiao Cheng; et al.
Abstract : A π‐conjugated Lewis base is introduced into perovskite solar cells, namely, indacenodithiophene end‐capped with 1.1‐dicyanomethylene‐3‐indanone (IDIC), as a multifunctional interlayer, which combines efficient trap‐passivation and electron‐extraction. Perovskite solar cells with IDIC layers yield higher photovoltages and photocurrents, and 45% enhanced efficiency compared with control devices without IDIC.